Peran Influencer Marketing Dalam Meningkatkan Brand Awareness dan Penjualan Produk Aftermyskin Pada Platform Media Sosial Tiktok - Siti Nur Aeni; Mariati Tirta Wiyata (Jurnal Ilmiah Global Education, 2026)
The rapid growth of social media has encouraged brands to adopt influencer marketing as a strategic approach to reach and engage digital consumers. TikTok, as one of the fastest-growing platforms in Indonesia, offers strong potential for increasing brand visibility and stimulating purchase behavior through its dynamic short-video format. Aftermyskin, a local skincare brand, leverages TikTok influencers to strengthen its presence among young audiences who actively consume digital content. This study aims to analyze the role of influencer marketing in enhancing brand awareness and improving sales performance on TikTok, while also examining the mediating effect of brand awareness. A quantitative research design was employed by integrating SEM-PLS analysis with actual TikTok Shop transaction data to obtain more accurate and comprehensive results. Consumer perceptions were collected through an online survey, and sales records were used to validate the predictive accuracy of the proposed model. The findings indicate that Influencer Marketing significantly increases Brand Awareness (β = 0.789; p < 0.001) and directly contributes to Sales (β = 0.327; p < 0.01). Brand Awareness further influences Sales (β = 0.512; p < 0.001) and functions as the primary mediating variable. The R² values of 0.623 and 0.681, supported by Q² values above 0.25, confirm the model’s robustness. Overall, the study concludes that TikTok influencer marketing is effective in expanding brand reach and enhancing the sales performance of Aftermyskin.